2013
DOI: 10.1111/nph.12168
|View full text |Cite
|
Sign up to set email alerts
|

Efficient xylem transport and phloem remobilization of Zn in the hyperaccumulator plant species Sedum alfredii

Abstract: SummarySedum alfredii is one of a few species known to hyperaccumulate zinc (Zn) and cadmium (Cd). Xylem transport and phloem remobilization of Zn in hyperaccumulating (HP) and nonhyperaccumulating (NHP) populations of S. alfredii were compared.Micro-X-ray fluorescence (l-XRF) images of Zn in the roots of the two S. alfredii populations suggested an efficient xylem loading of Zn in HP S. alfredii, confirmed by the seven-fold higher Zn concentrations detected in the xylem sap collected from HP, when compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 43 publications
4
61
0
1
Order By: Relevance
“…13 This pattern was also observed in Sedum alfredii, in which Zn was distributed mainly along the xylem. 14 The accumulation of Cr in Gynura pseudochina treated with Cr(III) was also located in the stem cortex and vascular bundle. Distribution, translocation and accumulation of Cr in G. pseudochina primarily depended on the oxidation state of Cr and on the plant tissue.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…13 This pattern was also observed in Sedum alfredii, in which Zn was distributed mainly along the xylem. 14 The accumulation of Cr in Gynura pseudochina treated with Cr(III) was also located in the stem cortex and vascular bundle. Distribution, translocation and accumulation of Cr in G. pseudochina primarily depended on the oxidation state of Cr and on the plant tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Researchers have found that increased xylem loading is the main factor affecting absorption and translocation of heavy metal from root to shoot; as shown in increasing uptake of Zn and Cd by S. alfredii, Solanum melongena, and Solanum torvum. 14,20 The xylem loading capacity of heavy metal hyperaccumulator plants is higher than in non-hyperaccumulator plants. 14,20 Hyperaccumulator plants also have special mechanisms to tolerate high concentration of heavy metals in tissue by using low-molecular-weight ligands, small metal-binding proteins such as histidine, organic acids, phytochelatine, metalothionine in the sequestration, transport, and accumulation of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that citrate and malate bind to Zn and Ni to allow for loading and unloading into and out of xylem, phloem and across the tonoplast. In Sedum alfredii, Lu et al (2013) showed increased levels of citrate in the xylem sap of plants from a hyperaccumulating population relative to a non-hyperaccumulating population and that the levels of citrate increased with increasing Zn concentration. Nickel hyperaccumulator Alyssum murale has increased citric acid and malic acid synthesis in the root mitochondria relative to non-hyperaccumulator A. montanum (Agrawal et al 2013).…”
Section: How Did Hyperaccumulation Evolve At the Molecular Level?mentioning
confidence: 97%